Cartoline dal fronte. La fotografia di guerra tra anestesia morale e pratica critica della trasparenza in Susan Sontag - Bottacin Cantoni, Lorenza (Scenari, 2024)
This essay examines Susan Sontag’s reflections on war photography. Beginning with the observation that much of the world’s conflict is invisible to us, while there are wars that we see in photographs and videos every day, Sontag analyzes the relationship between the beholder and the image that captures the pain and suffering of the others. The essay examines the evolution of Sontag’s thinking about photography from her initial understanding of it as an agent of moral anaesthetization and detachment from a concrete relationship to suffering. Sontag’s thinking turns out to be in part a precursor of Byung-Chul Han’s reflections on the palliative society. However, Sontag moves from an initially “apocalyptic” position of the medium of photography to a reassessment of photography as a critical art, as a medium that enhances empathy, but which must above all contribute to reflection. Only an unsentimental reflection on war photography can help to increase its capacity for protest and its impact on reality. The photographer makes himself transparent, takes away his agency and does not engage in war to show a part of the world; he risks his life to make suffering a source of moral action and of social change. In line with this position, Eyal Weizman also uses the medium of the image to call for instances of justice in war scenarios through forensic architecture.